Perception on genetic testing in Korean medicine doctors: A mobile-based survey - Sunju Park; Seong-Cheon Woo; Hyo-Jeong Ban; Siwoo Lee; Song-Yi Kim; Hee-Jeong Jin (Integrative Medicine Research)
Background: Currently, genetic testing is widely used to understand individual characteristics. In Korea, genetic testing has been in use, but not actively in Korean Medicine (KM). To examine the perceptions of genetic testing, we performed online survey to Korean Medicine doctors (KMDs). Methods: The survey was a mobile-based study that was developed by 6 survey specialists based on electronic database search results. The questionnaire consisted of 6 categories: general characteristics of respondents, understanding of genetic testing, demand for using genetic testing, application field and utilization level of genetic testing, limitations of genetic testing, and plans and necessary efforts to begin using genetic testing based on an 11-point Likert scale. Results: With the response rate of 27.2% (n = 544), 46.9% of respondents answered that they understood the definition and mechanism of genetic testing. About 80% of KMDs responded that they would be willing to use genetic testing results; a notable reason for this was the need for more objective and evidence-based test results. KMDs recognized that genetic testing could not only provide personalized treatment and care, but also help communicate with patients. Conclusions: This study observed KMDs’ perceptions of the potential clinical benefits of genetic testing. We confirmed that development of genetic testing technology, knowledge of their use, and new technology-friendly policies are essential for expanding the genetic testing technology in Korean medicine.